Efectiveness of Celery (Apium Graveolens) on Hppertension in The Elderly - Rupdi Lumban Siantar; Farida Mentalina Simanjuntak; Tetty Rina Aritonang (Institute of Computer Science (IOCS), 2021)
Hypertonia, after stroke and tuberculosis, is the third leading cause of death. It is a degenerative condition in the elderly when nearly everyone sees a rise in blood pressure as they age. Treatment of hypertension may be pharmacological or nonpharmacological. Pharmaceutical therapy is often deemed prohibitively costly by others, prompting some to seek nonpharmacological care, including herbal medicine, which includes the use of celery. Celery is the most frequently seen plant in the neighborhood. Celery contains apigenin, which is beneficial for reducing blood flow narrowing and hypertension. This study aims to determine the efficacy of celery in treating hypertension, especially in elderly patients at the Matraman District Health Center. The study employed an unconventional one-group pretest-posttest setup with a control group. The sample size was five individuals, and the research was conducted using comparative analysis and paired t-tests using computerized statistical tools. The findings indicated a discrepancy in blood pressure both before and after the elderly were given celery, although the difference was not statistically meaningful.